Expanding the Use of SGLT2 Inhibitors in T2D Patients Across Clinical Settings - Alessandro Cuttone; Vittorio Cannavò; Raouf Mastan Sheik Abdullah; Pierluigi Fugazzotto; Giada Arena; Simona Brancati; Andrea Muscarà; Carmela Morace; Cristina Quartarone; Domenica Ruggeri; Giovanni Squadrito; Giuseppina Tiziana Russo (Cells)
Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are currently recommended in patients with type 2 diabetes (T2D) to reduce serum glucose levels. Moreover, robust evidence has clearly demonstrated their beneficial cardiovascular and renal effects, making this class of drugs pivotal for the treatment of T2D, especially when complicated by diabetic kidney disease or heart failure. However, several other comorbidities are frequently encountered in T2D patients beyond these long-term diabetes complications, especially in the internal medicine setting. For some of these comorbidities, such as MAFLD and cognitive impairment, the association with diabetes is increasingly recognized, with the hypothesis of a common pathophysiologic background, whereas, for others, a coincident epidemiology linked to the ageing of populations, including that of T2D subjects, may be advocated. In the effort of personalizing T2D treatment, evidence on the potential effects of SGLT2i in these different clinical conditions is accumulating. The purpose of this narrative review is to update current literature on the effects of SGLT2i for the treatment of T2D in different clinical settings beyond glycaemic control, and to elucidate potential molecular mechanisms by which they exert these effects.